Analisis Tinjauan Tantangan dan Peluang Penerapan Dasar Ilmu Al-Qur’an pada Remaja dalam Era Society 5.0 - Fatihul Ihsan (Lembaga Pengembangan Kinerja Dosen, 2025)
The emergence of Society 5.0, which integrates advanced technologies into human-centered systems, significantly influences adolescents’ learning patterns and religious engagement, particularly in studying fundamental Qur’anic sciences. This research aims to analyze the challenges and opportunities in applying Qur’anic knowledge among adolescents within this socio-digital environment. A descriptive qualitative method was employed, involving interviews, participant observations, and literature review. The findings indicate several challenges, including low motivation, the dominance of instant digital culture, limited spiritually oriented digital literacy, and insufficient guidance from families and educators. Most adolescents primarily use technology for entertainment, leading to shallow understanding of tajwīd, basic tafsīr, and contextual revelation. However, the study also identifies substantial opportunities through AI-based Qur’an applications, gamification, educational videos, and interactive learning platforms that effectively enhance adolescents’ interest and comprehension. Contextual pedagogical approaches that relate Qur’anic values to contemporary issues further increase relevance. The study concludes that integrating modern technology with creative pedagogical strategies can strengthen adolescents’ Qur’anic literacy amid the challenges of the Society 5.0 era.